The Use of Audio-Visual Media on Student Learning Interest in Explanatory Text Material - Bawamenewi, Arozatulo; Lase, Julita Hertawati; Zega, Elsa Fitriana; Gea, Lince Imerda (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The use of audio-visual media in education has gained increasing attention due to its potential to enhance student engagement and learning outcomes. In Indonesian language instruction, particularly in teaching explanatory text material, there is a need to explore innovative methods to improve student interest and comprehension. Purpose. This study aims to evaluate the impact of using audio-visual media on students' interest in learning explanatory text material in class VII-A SMP Negeri 2 Hiliduho. Method. A qualitative research method with a descriptive approach was employed. The study involved 20 students from class VII-A SMP Negeri 2 Hiliduho. Data were collected through observation, interviews, and documentation techniques. Results. The use of audio-visual media significantly increased students' interest and understanding of explanatory text material. Students demonstrated improved ability in determining appropriate terms and adjusting explanatory texts to their proper structure and characteristics. Audio-visual media, such as PowerPoint presentations and videos, made the material more engaging and comprehensible, facilitating a more efficient learning process. Students using audio-visual media showed higher levels of engagement compared to those who did not, as they were able to follow the learning flow more effectively. Conclusion. The findings suggest that audio-visual media play a crucial role in enhancing the learning experience for students studying explanatory text material. Teachers reported that these tools aided in more effective content delivery. The increased student engagement and improved understanding of the material highlight the potential of audio-visual media as a valuable instructional tool in Indonesian language education, particularly for explanatory text instruction.